Associative Characteristics of the Proverb (Zien Journal of Social Sciences and Humanities, 2022)
In the article it is about the proverb, as a kind of the speech: one evaluates the criteria to characterize the statute of the kind of the speech of the proverb; these criteria are clarified by noting the prototypical defining characteristics of the proverbial genre; we explain the proverbial construction and the figures of speech which present the theory of the actualization of proverbs.